International journal of automotive engineering : official journal of the Society of Automotive Engineers of Japan, Inc - Jidōsha Gijutsukai (The Society of Automotive Engineers of Japan, 2010)
"The International Journal of Automotive Engineering (IJAE) is an Open Access journal publishing rigorous theoretical and applied research in all areas of automotive engineering. The official journal of the Society of Automotive Engineers of Japan, Inc., IJAE welcomes submissions from around the world. IJAE is a journal aiming to publish and electronically disseminate high-quality original papers in all aspects of automotive engineering, technology, and science. IJAE is an effective platform for facilitating the exchange of information on new concepts, methodology, and recent progress in the automotive research and development communities. The Journal is published quarterly (January, April, July, and October) by the Society of Automotive Engineering of Japan, IJAE welcomes submissions from all around the world, especially those that promote information exchange between academia and industry. The main topics are : engine and power sources ; power transmission ; EV and HV systems ; vehicle dynamics and development ; vibration, noise, and ride comfort ; safety ; human engineering ; thermofluidic dynamics ; environment, energy, and resources ; materials, production and manufacturing ; control electronics ; control in information and communication technology ; social systems ; common infrastructure."--taken from issuing body's website viewed April 4, 2023.
Keywords: Automobiles : Design and construction : Periodicals; Automobiles : Technological innovations : Periodicals; Human engineering : Periodicals; Automobiles : Safety measures : Periodicals; Automobile driving : Human factors : Periodicals; Driver assistance systems : Periodicals; Automobiles : Testing : Computer simulation : Periodicals; Automobiles : Motors : Design and construction : Periodicals; Automobiles : Motors : Technological innovations : Periodicals; Motor vehicles : Design and construction : Periodicals; Automated vehicles : Design and construction : Periodicals; Electric vehicles : Design and construction : Periodicals; Alternative fuel vehicles : Design and construction : Periodicals; Automobile driving : Human factors; Automobiles : Design and construction; Automobiles : Motors : Design and construction; Automobiles : Motors : Technological innovations; Automobiles : Safety measures; Automobiles : Technological innovations; Driver assistance systems; Electric vehicles : Design and construction; Human engineering; Motor vehicles : Design and construction